Determinants of Bank Performance: Evidence from Non-Performing Loans (NPL), Net Interest Margin (NIM), Allowance for Impairment Losses (AIL), and Deferred Tax Expense - Rimet Rimet; Nuraini Nuraini; Arfah Piliang; Ramadahniel Islami (Research in Accounting Journal (RAJ), 2026)
This study investigates the impact of Non-Performing Loans (NPL), Net Interest Margin (NIM), Allowance for Impairment Losses (AIL), and Deferred Tax Expense on the financial performance of conventional commercial banks listed on the Indonesia Stock Exchange (IDX) over the period 2021–2023. Employing a quantitative approach with panel data regression and purposive sampling, 24 banks yielding 72 observations were estimated via the Random Effect Model (REM). Results reveal that NPL exerts a significant negative effect on financial performance, whereas AIL and Deferred Tax Expense demonstrate significant positive effects. NIM, however, shows no significant influence. The model accounts for 24% of the variance in financial performance, suggesting that credit risk management and tax-related accounting components are critical determinants of bank profitability in emerging markets.